การดูแลบิดามารดาสูงอายุตามหลักคำสอนในพระพุทธศาสนาของครอบครัวไทยพุทธ / Caregiving for Elder Parents in Accordance with the Buddhist Doctrine in Thai Buddhist Families - Somboon Watana, สมบูรณ์ วัฒนะ / (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 2 (2560): April-June 2017, 2017)
งานวิจัยนี้มีวัตถุประสงค์เพื่อศึกษาการดูแลบิดามารดาสูงอายุตามหลักคำสอนในพระพุทธศาสนาของครอบครัวไทยพุทธ รูปแบบการวิจัยเป็นการวิจัยเชิงปริมาณ ประชากรในการศึกษา คือ ผู้นับถือศาสนาพุทธที่มีอายุ 18-59 ปี อาศัยอยู่ในเขตกรุงเทพมหานคร สุ่มตัวอย่างแบบเจาะจง เลือกเขตพื้นที่ศึกษา 5 เขต เก็บข้อมูลโดยใช้แบบสอบถามผู้นับถือพระพุทธศาสนาจำนวน 632 คน วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา ผลการศึกษา พบว่า กลุ่มตัวอย่างไทยพุทธร้อยละ 98.4 ตอบว่า “ใช่” คือ เห็นด้วยในเรื่องการดูแลบิดามารดาสูงอายุตามที่ได้รับสืบทอดกันมาตามแนวคำสอนทางพระพุทธศาสนา เช่น เห็นว่าการดูแลบิดามารดาสูงอายุเป็นหน้าที่สำคัญอย่างหนึ่งตามหลักคำสอนเรื่องกตัญญูในพระพุทธศาสนา และการดูแลบิดามารดาที่สูงอายุเป็นมงคล คือ สิ่งที่ดีงามอย่างหนึ่งตามคำสอนของพระพุทธศาสนา เป็นต้น และร้อยละ 95.5 ตอบรับว่า “ใช่” คือ ได้ปฏิบัติตนในการดูแลบิดามารดาสูงอายุตามหลักคำสอนเรื่องภาวนา 4 ในพระพุทธศาสนา เช่น การเอาใจใส่ในเรื่องสุขอนามัย ดูแลเมื่อเจ็บป่วย ส่งเสริมและยินดีให้ท่านได้ปฏิบัติสมาธิ สวดมนต์ ฟังธรรมเทศนา เป็นต้น      This research has aimed to study on the caregiving for elderly parents in accordance with the Buddhist doctrine in Thai Buddhist families. It is a quantitative research targeting to the Buddhist population of aged between 18–59 years old who had been living in the 5 target districts of Metropolitan Bangkok, Thailand. A purposive sampling technique was used to identify and gathering the data from 632 sample population with the application of a descriptive statistic for data analysis. The findings revealed that 98.4 % of the samples agreed upon the influence of traditional Buddhism teaching regarding the caregiving for elderly parents. For instance, it taught that caregiving for parents is an essential duty of any children as well as it is an auspicious mandate that Thai Buddhist must do in order to be grateful and reciprocate with our parents. There are about 95.5% of the samples agreed to follow the principle of caregiving for elderly parents in relation to the Buddhist doctrine of  Bhavana  4 (4 dimensions of man development) such as caregiving for health promotion or on sickness, to support for practicing mediation, chanting, listening the  dhamma  talk in various occasion etc.
Keywords: การดูแลบิดามารดาสูงอายุ หลักคำสอนในพระพุทธศาสนา ครอบครัวไทยพุทธ; Elder Parents Care, Buddhist Doctrine, Thai Buddhist Families